Strength, Fracture and Durability Characteristics of Ambient Cured Alkali—Activated Mortars Incorporating High Calcium Industrial Wastes and Powdered Reagents - Dhruv Sood; Khandaker M. A. Hossain (Crystals, 2021)
Alkali-activated mortars (AAMs) are developed incorporating binary/ternary combinations of industrial wastes comprising of fly ash class C (FA-C), fly ash class F (FA-F) and ground granulated blast furnace slag (GGBFS) with alkaline reagents and silica sand. The use of high calcium precursors, calcium-based powder form reagents, dry mixing method, and ambient curing with performance characterization based on chemical ratios and fracture properties are some novel aspects of the study. The mechanical (dry density, compressive strength, ultrasonic pulse velocity, elastic modulus, fracture/crack tip toughness and fracture energy), durability (shrinkage/expansion and mass change in water and ambient curing conditions, water absorption and freeze-thaw resistance) and microstructural (SEM/EDS and XRD analyses) characteristics of eight AAMs are investigated. The binary (FA-C + GGBFS) mortars obtained higher compressive strengths (between 35 MPa and 42.6 MPa), dry densities (between 2032 kg/m3 and 2088 kg/m3) and ultrasonic pulse velocities (between 3240 m/s and 4049 m/s) than their ternary (FA-C + FA-F + GGBFS) counterparts. The elastic modulus and fracture toughness for mortars incorporating reagent 2 (calcium hydroxide: sodium sulphate = 2.5:1) were up to 1.7 and five times higher than those with reagent 1 (calcium hydroxide: sodium metasilicate = 1:2.5). This can be attributed to the additional formation of C-S-H with C-A-S-H/N-C-A-S-H binding phases in mortars with reagent 2. Ternary mortars exhibited comparatively lower shrinkage/expansion and initial sorptivity indices than their binary counterparts due to the lower geopolymerisation potential of fly ash class F that facilitated the reduction of matrix porosity. All mortar specimens demonstrated 100% or more relative dynamic modulus of elasticity after 60 freeze-thaw cycles, indicating the damage recovery and satisfactory durability due to probable micro-level re-arrangement of the binding phases. This study confirmed the viability of producing cement-free AAMs with satisfactory mechanical and durability characteristics.